LINE BALANCING ANALYSIS BY USED RANK POSITIONAL WEIGHT (RPW) (CASE STUDY: PART BODY S11038Z PROCESS) - Supriyono, Supriyono; Suryanto, Dwi; Hendra, Franka; Effendi, Riki (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2020)
The purpose of this paper is to determine the number of proposed work stations based on Rank Positional Weight and to find out the results of the comparison between the initial work station conditions and the proposed work station conditions. The method used in optimizing Line Balancing is the Rank Positional Weight (RPW) method by calculating the amount of processing time, Balance Delay, Smoothness Index, the largest track efficiency, and station efficiency. The results of the comparison between the initial work station conditions and the proposed work station conditions using the RPW method in the total production process time of the S11038Z section from the initial conditions of 1060.23 seconds after analysis using the RPW method obtained a shorter processing time of 970.23 seconds or reduced by 90 seconds. The balance delay in the initial condition was 67.6% with the RPW method, the result was that the balance delay was better, namely 62.9%. The smoothness index in the initial conditions is 1059.79 to 857.88. The tracking efficiency increased by 4.7%, from 32.4% to 37.1%. The efficiency of the biggest workstations also increased, from 489 seconds to 399 seconds.